The Next smart step : how to overcome gender stereotypes and build a stronger organization - Watson, Kelly; Detjen, Jodi Ecker (Watertown, MA : Charlesbridge, 2021)
Empowering women empowers everyone. Women with confidence, equal pay, and leadership opportunity enrich workplace culture and help the whole organization. The first step is understanding that gender balance is not a zero-sum game. The Next Smart Step is a clear, assured guide to understanding the challenge of gender imbalance, implementing solutions, and equipping readers with the tools we all need to ensure change that is positive and enduring. It is about all of us becoming leaders.
The challenge: barriers and bias -- It's all made up -- Unconscious bias -- Flawed assumptions and bad habits -- Organizational bias -- The solution: reframe and renew -- The power of the reframe -- What women need to do -- What men need to do -- What organizations need to do -- Making gender equity happen: tools and techniques -- Promoting leadership -- Building gender equity from vision to reality -- Making and measuring progress -- Conclusion -- Postscript -- Acknowledgments -- Appendences -- Bibliography -- Endnotes -- Index -- About the Authors.
Includes bibliographical references.
Keywords: CORPORATE CULTURE